WOMANDLA! Women Power! - Miller, Rolene (Book collections on Project MUSE., 2018)
Rolene Miller registered Mosaic, Training, Service and Healing Centre to empower abused women, and like a Mosaic 'to put the broken pieces of their lives together and make their lives more beautiful,' Womandla! Women Power! is an account of Mosaic's Community Workers' and Court Workers' lives, training and services and Rolene's writings describing the journey. Their humour and laughter is present whilst constantly moving through the difficult days at Mosaic. This book describes Mosaic's support from our caring God. It is a human story where honest values are realised and people's lives are changed forever. It is for readers who want to know the 'Herstory' of a ground-breaking and innovative Mosaic working with abused women for 25 successful years and still surviving today. 'Womandla! Women Power!' belongs to everyone who in our patriarchal culture and society wants to prevent and stop Women Abuse and Domestic Violence and who needs to seriously and critically condemn it.